Extraction and Application of Natural Dye from African Locust Bean (Parkia biglobosa) Pod on Nylon Fabrics - Andema Aaron Kanadi; Abdulkadir Junior Bilyamin; Joshua Yakubu; Lunsti John; Akinterinwa Ayo; Peter Micheal Dass (African Journal of Biochemistry and Molecular Biology Research, 2026)
Growing environmental and health concerns regarding synthetic dyes have increased interest in natural colorants as potentially more sustainable alternatives. This study aimed to extract and optimize a natural dye from Parkia biglobosa pods and evaluate its application to nylon fabrics. The dye was extracted through maceration, producing a yield of 23.76%. The optimum dyeing conditions for treated and untreated nylon were concentrations of 1% and 1.5%, temperatures of 60 and 70 °C, and dyeing times of 30 and 40 min, respectively. The extract was applied using pre-, meta-, and post-mordanting techniques with copper sulfate, ferrous sulfate, and potassium aluminum sulfate as mordants. The resulting fabrics exhibited shades ranging from light and dark brown to black, with pre-mordanting producing the most visually attractive shades. However, the dyed nylon fabrics demonstrated poor colorfastness to sunlight and washing, with ratings ranging from 1 to 3. Neither mordanted nor unmordanted fabrics exhibited antibacterial activity against B. subtilis or S. Typhi (inhibition zone: 0.00 ± 0.00 mm). In contrast, all dyed fabrics showed varying antifungal activity against P. notatum. Treated nylon dyed with copper sulfate produced the largest inhibition zone (1.0 ± 0.00 mm), whereas untreated nylon dyed with potassium aluminum sulfate produced the smallest (0.3 ± 0.00 mm). These findings demonstrate the potential of P. biglobosa pods as a source of natural dye for nylon fabrics, particularly when applied through pre-mordanting. Nevertheless, the poor colorfastness and limited antimicrobial performance indicate that further optimization is necessary before practical textile application.